Work Relative Value Units Do Not Adequately Support the Burden of Infection Management in Revision Knee Arthroplasty. (5th February 2020) - Samuel, Linsen T.; Grits, Daniel; Acuña, Alexander J.; Piuzzi, Nicolas S.; Higuera-Rueda, Carlos A.; Kamath, Atul F.
Abstract : Background: Revision total knee arthroplasty for infection is challenging. Septic revisions, whether 1-stage or 2-stage, may require more time and effort than comparable aseptic revisions. However, the burden of infection may not be reflected by the relative value units (RVUs) assigned to septic revision compared with aseptic revision. The purposes of this study were to compare the RVUs of aseptic and septic revision total knee arthroplasties and to calculate the RVU per minute for work effort. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database was analyzed for the years 2006 to 2017. The Current Procedural Terminology (CPT) code 27487 and the International Classification of Diseases, Ninth Revision (ICD-9) code 996.XX, excluding 996.6X, were used to identify all aseptic revision total knee arthroplasties (n = 12, 907). The CPT code 27487 and the ICD-9 code 996.6X were used to determine all 1-stage septic revision total knee arthroplasties (n = 891). The CPT codes 27488 and 11981 were used to identify the first stage of a 2-stage revision (n = 293). The CPT codes 27447 and 11982 were used to identify the second stage of a 2-stage revision (n = 279). After 4:1 propensity score matching, 274 cases were identified per septic cohort (aseptic single-stage: n = 1, 096). The RVU-to-dollar conversion factor was provided by the U.S. Centers for Medicare & Medicaid Services (CMS), and RVU dollar valuations were calculated. Results: The septic second-stage revision was used as the control group for comparisons. The RVU per minute for the aseptic 2-component revision was 0.215, from a mean operative time of 148.95 minutes. The RVU per minute for the septic, 2-component, 1-stage revision was 0.199, from a mean operative time of 160.6 minutes. For septic, 2-stage revisions, the first-stage RVU per minute was 0.157, from a mean operative time of 138.1 minutes. The second-stage RVU per minute was 0.144, from a mean operative time of 170.0 minutes. Two-component aseptic revision total knee arthroplasty was valued the highest. Conclusions: Despite the increased complexity and worse postoperative outcomes associated with revision total knee arthroplasties for infection, the current physician reimbursement does not account for these challenges. This inadequate compensation may discourage providers from performing these operations and, in turn, make it more difficult for patients with periprosthetic joint infection to receive the necessary treatment. Therefore, the CPT code revaluation may be warranted for these procedures.